2017
DOI: 10.1103/physreva.95.063413
|View full text |Cite
|
Sign up to set email alerts
|

Vibrationally assisted below-threshold ionization

Abstract: We perform time-resolved UV pump (4.77 eV) and VUV probe (7.94 eV) measurements of internal conversion of 1,3-cyclohexadiene (CHD). Our measurements reveal a substantial ionization of the "hot" ground state following internal conversion despite the fact that our probe photon energy is below the ionization potential (8.21 eV). With the aid of electronic structure calculations, we interpret our results in terms of vibrationally assisted below threshold ionization, where vibrational energy is converted to electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…AKEs were computed on top of the triplet state minima for the first time, triplet to doublet gaps being extremely large, making the probe pulses here employed (5.2 eV) unable to ionise the systems (Cyd being the only case ionised with an AKE B 0.08 eV) and thus suggesting the move to even more energetic probe pulses (vacuum UV) for their characterization. 103 The CT state, on the other hand, shows smaller singlet to doublet gaps, readily accessible for photoelectron studies with less energetic probe pulses. Our estimates reveal larger AKEs to those found in the FC region for all systems, being B3 eV and over an eV larger than those registered for FC, and even larger towards the CI with the ground state, thus being a unique fingerprint for their characterization.…”
Section: Spectral Signalsmentioning
confidence: 99%
“…AKEs were computed on top of the triplet state minima for the first time, triplet to doublet gaps being extremely large, making the probe pulses here employed (5.2 eV) unable to ionise the systems (Cyd being the only case ionised with an AKE B 0.08 eV) and thus suggesting the move to even more energetic probe pulses (vacuum UV) for their characterization. 103 The CT state, on the other hand, shows smaller singlet to doublet gaps, readily accessible for photoelectron studies with less energetic probe pulses. Our estimates reveal larger AKEs to those found in the FC region for all systems, being B3 eV and over an eV larger than those registered for FC, and even larger towards the CI with the ground state, thus being a unique fingerprint for their characterization.…”
Section: Spectral Signalsmentioning
confidence: 99%
“…The ring-opening dynamics of CHD after excitation from the HOMO to the lowest unoccupied molecular orbital via one-photon absorption (1PA) is one of the most actively studied dynamics in time-resolved spectroscopy [26,27,[29][30][31][32][33][34][35][36][37][38][39][40]. Most studies reported that the ring-opening step in the isomerization process is completed in less than 200 fs after photoexcitation.…”
Section: Ultrafast Photo-isomerization Of 13-cyclohexadienementioning
confidence: 99%
“…76 This makes use of an established methodology producing the fifth harmonic of a Ti:Sapphire laser (160 nm) in a static gas cell via non-collinear four-wave mixing. 77,78 Such an approach has also been demonstrated previously for use as a probe in other time-resolved studies of non-adiabatic molecular processes, [79][80][81][82] as have related variations employing the sixth harmonic (133 nm) [83][84][85][86] and ninth harmonic (90 nm). 87 To undertake experiments using a VUV probe beam, an auxiliary differentially pumped vacuum chamber is incorporated into the existing VMI spectrometer from Fig.…”
Section: Extending the View Along The Reaction Coordinatementioning
confidence: 92%